Comprehensive mechanical characterization of PLA fabric combined with PCL to form a composite structure vascular graft. (May 2017) - Li, Chaojing; Wang, Fujun; Douglas, Graeham; Zhang, Ze; Guidoin, Robert; Wang, Lu
Abstract: Vascular grafts made by tissue engineering processes are prone to buckling and twisting, which can impede blood flow and lead to collapse of the vessel. These vascular conduits may suffer not only from insufficient tensile strength, but also from vulnerabilities related to compression, torsion, and pulsatile pressurization. Aiming to develop a tissue engineering-inspired blood conduit, composite vascular graft (cVG) prototypes were created by combining a flexible polylactic acid (PLA) knitted fabric with a soft polycaprolactone (PCL) matrix. The graft is to be populated in-situ with cellular migration and proliferation into the device. Comprehensive characterizations probed the relationship between structure and mechanical properties of the different cVG prototypes. The composite grafts exhibited major improvements in mechanical characteristics compared to single-material devices, with particular improvement in compression and torsional resistance. A commercial expanded polytetrafluoroethylene (ePTFE) vascular graft was used as a control against the proposed composite vascular grafts. CVG devices showed high tensile strength, high bursting strength, and improved suture retention. Compression, elastic recovery, and compliance were similar to those for the ePTFE graft.